THE IMPACTS OF DEVELOPMENTAL DYSLEXIA ON THE PRACTICE OF SECOND LANGUAGE DYSLEXIC TEACHERS - Fay de Azevedo, Aline (2020)
Dyslexia is a learning disorder and a neurobiological condition, which means it affects areas of the brain that process language. Dyslexic teachers carry the struggles caused by dyslexia with them to the workplace. Despite the fact that dyslexia may not be considered a positive characteristic, dyslexic teachers show more empathy towards their pupils with learning disabilities and make use of creative coping strategies, which help them overcome their own learning disability in the classroom. Taking these aspects into consideration, the present article was developed with the purpose of throwing light on dyslexic teachers and the impacts of dyslexia in their practice. The aim of this theoretical study was to define dyslexia and to present an overview of this learning disability. Furthermore, we intended to investigate through bibliographical research how dyslexia affects second language teachers in their classroom practice and workplace. To present some strategies teachers can use to cope with dyslexia. Lastly, to design a pamphlet to be used as a guideline for dyslexic teachers.Keywords: dyslexia; dyslexic teachers; foreign language learning; learning disabilities.